Peran edukasi interaktif dalam peningkatan pengetahuan kesehatan gigi dan mulut - Shalsabilla A. Hi. Yahya, Putri; Asia, Rr. Asyurati; Juliawati, Mita; Suwartini, Tien; Cloudya Panjaitan, Caesary (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Oral and dental health is an important aspect of body health that is often neglected. Many research data show that the level of awareness and optimal oral and dental health practices still need to be improved. This improvement requires oral and dental health education with more interesting methods and can involve active participation from the audience. Objective: to assess an overview of Family Welfare and Empowerment Organization knowledge regarding dental and oral health before and after education using interactive media. Methods: This study was a quasi experimental study with a pre-test – post-test conducted on PKK women in Palu, Sulawesi Tengah. The PKK women knowledge was measured by filling out the questionnaire, which has been tested for its validity and reliability using the Pearson product moment correlation and Cronbach Alpha, then the questionnaires were distributed directly. Results: An assessment involving 91 respondents demonstrated a consistent upward trend in dental and oral health knowledge among most PKK women, observed prior to counseling and sustained at 15-day and 30-day post-intervention intervals. Conclusion: This study shows that most PKK women experienced increased knowledge about maintaining oral health. PKK women need to be more active in providing information related to oral health and are expected to practice it daily for themselves and their families. Interactive educational media is an effective tool for oral health education and increasing knowledge, especially among community groups such as PKK women. These findings support its broader implementation in public health programs to address preventable oral health problems.